Comparative impact analysis of nitrate reduction by typical components of natural organic compounds in magnetite-bearing riparian zones - Jia Niu; Yuyu Wan; Zhe Ma; Weihong Dong; Xiaosi Su; Yuanzheng Zhai; Xiaofang Shen; Xiaokun Yi (Ecotoxicology and Environmental Safety)
As the key interface, the nitrate removal capacity of riparian zones is receiving close attention. Although naturally occurring organic compounds in this environment play a pivotal role in shaping microbial communities and influencing the nitrate removal capacity, the relevant research is inadequate. Given the complexity of riparian environments, in this study, we added representative natural organic matter (fulvic acid, butyric acid, naphthalene, starch, and sodium bicarbonate) as carbon conditions and incorporated magnetite to simulate riparian zone components. The study investigated the nitrate degradation efficiency and microbial responses under different natural carbon conditions in real iron-containing environments. Butyric acid exhibited the most efficient nitrate reduction, followed in descending order by naphthalene, starch, sodium bicarbonate, and humic acid. However, this did not imply that butyric acid efficiently removed nitrogen; instead, the nitrogen would circulate in the environment in the form of ammonium. Denitrification and DNRA were the primary drivers of nitrate reduction in each system, while naphthalene and humic acid systems also exhibited nitrification and mineralization. Nitrogen-fixing bacteria represent a unique microbial community in the butyrate system. Further, the synergistic degradation of naphthalene and nitrate demonstrated significant potential applications. High-throughput sequencing revealed that carbon conditions exerted selective pressure on microorganisms, driving Fe (Ⅱ)/Fe (Ⅲ) transformation by shaping the microbial community structure and influencing the nitrogen cycling process.